2019
DOI: 10.1021/acs.biochem.9b00441
|View full text |Cite
|
Sign up to set email alerts
|

q and the Phospholipase Cβ3 X–Y Linker Regulate Adsorption and Activity on Compressed Lipid Monolayers

Abstract: Phospholipase Cβ (PLCβ) enzymes are peripheral membrane proteins required for normal cardiovascular function. PLCβ hydrolyzes phosphatidylinositol 4,5-bisphosphate, producing second messengers that increase intracellular Ca2+ level and activate protein kinase C. Under basal conditions, PLCβ is autoinhibited by its C-terminal domains and by the X–Y linker, which contains a stretch of conserved acidic residues required for interfacial activation. Following stimulation of G protein-coupled receptors, the heterotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
0
6
1
Order By: Relevance
“…the distal C-terminal domain is a coiled-coil domain with highly conserved clusters of lysine and arginine residues arrayed along one face that function as a major membrane binding determinant. Indeed, the membrane acts as an allosteric activator of PLCs [198,199]. Thus conceptually, the model that PLCβ3 only hydrolyzes ORP4L-extracted lipid is at odds with our general understanding of how PLCβ enzymes work in general.…”
Section: Plcβ3mentioning
confidence: 99%
“…the distal C-terminal domain is a coiled-coil domain with highly conserved clusters of lysine and arginine residues arrayed along one face that function as a major membrane binding determinant. Indeed, the membrane acts as an allosteric activator of PLCs [198,199]. Thus conceptually, the model that PLCβ3 only hydrolyzes ORP4L-extracted lipid is at odds with our general understanding of how PLCβ enzymes work in general.…”
Section: Plcβ3mentioning
confidence: 99%
“…On the basis of the current evidence, the release of autoinhibitory interactions in PLCγ enzymes is mediated by protein-protein interactions and phosphorylation of the key tyrosine residue (Y783 in PLCγ1) ( 1 ). In the PLCβ family, an additional role of the membrane interface in activation has been extensively studied ( 16 , 21 , 22 , 51 , 52 ). Specifically, a large cluster of acidic residues in the XY-linker occludes the active site and could be displaced in the proximity of the negatively charged membrane to enable access to PIP 2 substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive analyses of some of the PLC enzymes also identified specific features involved in regulation of a particular family and suggested that membrane interactions could be quite complex, with multiple roles. In this respect, members of the PLC family have been studied most extensively; in addition to structural studies (13)(14)(15)(16)(17), regulation of these enzymes has been analyzed in the presence of different model membranes in vitro (21)(22)(23)(24)(25). In its basal state, PLC is autoinhibited by the XY-linker from the catalytic TIM barrel and by elements from the C-terminal domain, representing a unique feature of PLC enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…However, substitution of these residues to negatively charged amino acids had no effect on the basal enzymatic activity of PLCβ4, suggesting that the mechanism of D630-mutant GOF phenotypes does not involve interaction with these residues. Furthermore, PLCβ4(D630Y) retained the GOF phenotype with deletion of either the unstructured amino terminus, the acidic stretch, or the structured carboxyl-terminal X-Y linker ( 38 , 52 ). Therefore, the constitutive activity of PLCβ4(D630Y) does not seem to involve regulation of the autoinhibitory X-Y linker.…”
Section: Discussionmentioning
confidence: 99%